2003
DOI: 10.1002/jnr.10847
|View full text |Cite
|
Sign up to set email alerts
|

Transient focal ischemia in rat brain differentially regulates mRNA expression of protease‐activated receptors 1 to 4

Abstract: Degeneration or survival of cerebral tissue after ischemic injury depends on the source, intensity, and duration of the insult. In the model of focal ischemia, reduced blood flow results in a cascade of pathophysiologic events, including inflammation, excitotoxicity, and platelet activation at the site of injury. One serine protease that is associated closely with and produced in response to central nervous system (CNS) injury is thrombin. Thrombin enters the injury cascade in brain either via a compromised bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 51 publications
(85 reference statements)
3
32
0
1
Order By: Relevance
“…This consists of cDNA reverse transcribed from mRNA pooled from three rat hearts. Forward and reverse primers used for amplifying rat PAR4 were prepared commercially, based on published data (Rohatgi et al, 2004): sense, 5Ј-GGA ATG CCA GAC GCC CAG CAT C-3Ј; and antisense, 5Ј-GGT GAG GCG TTG ACC ACG CA-3Ј (PCR product, 559 bp). The conditions for amplification were 95°C for 10 min for one cycle, 94°C for 30 s, 64°C for 90 s, 72°C for 60 s for 40 cycles, and 72°C for 10 min for 1 cycle.…”
Section: Methodsmentioning
confidence: 99%
“…This consists of cDNA reverse transcribed from mRNA pooled from three rat hearts. Forward and reverse primers used for amplifying rat PAR4 were prepared commercially, based on published data (Rohatgi et al, 2004): sense, 5Ј-GGA ATG CCA GAC GCC CAG CAT C-3Ј; and antisense, 5Ј-GGT GAG GCG TTG ACC ACG CA-3Ј (PCR product, 559 bp). The conditions for amplification were 95°C for 10 min for one cycle, 94°C for 30 s, 64°C for 90 s, 72°C for 60 s for 40 cycles, and 72°C for 10 min for 1 cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Because PAR4 is also expressed on neurons, it is also possible that inhibiting expression of PAR4 in the brain has a direct neuroprotective effect after brain ischemic injury. Other studies also showed that PAR4 mRNA levels were found to be significantly increased 12 h after ischemia in the rat injured hemisphere and this increased level was reduced only after 7 days (Rohatgi et al, 2004). Because PAR4 receptors are widely distributed and deficiency of PAR4 showed multiple effects in cerebral I/R injury, it is still difficult to determine the exact mechanisms through which PAR4 acts.…”
Section: Par4 Deletion Attenuates Cerebral Ischemic Injurymentioning
confidence: 99%
“…More recently, PAR1 deficiency in a PAR1 knockout mouse has been demonstrated to be protective against renal failure in a model of renal I/R [24]. Even though PAR1 is expected to be activated by thrombin at the time of myocardial injury, little is known about its role in determining the extent of myocardial I/R injury.…”
Section: Introductionmentioning
confidence: 99%